Positive electrode material for photovoltaic lithium-sulfur battery as well as preparation method and application of positive electrode material
By using a combination of carbon nanotube matrix and molybdenum carbide nanoparticles in the cathode material of lithium-sulfur batteries, the problem of polysulfide shuttle effect during the charge and discharge process of lithium-sulfur batteries is solved, and the high rate and long cycle performance of the battery are achieved. .
Patent Information
- Application Number
- CN202411330740.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-24
AI Technical Summary
The shuttle effect caused by polysulfides during the charging and discharging of lithium sulfur batteries leads to loss of active substances and deterioration of the surface environment of lithium negative electrodes, hindering the high capacity and long circulation performance of the battery.
The carbon nanotuba is used as a substrate material, and the carbonized two molybdenum nanoparticles are deposited in the inside and outside of the carbon nanotuba. The polysulfide is dissolved into the ether electrolyte through physical and chemical effects to improve the shuttle effect of the polyphenide.
Effectively suppress the shuttle effect of multi -sulfide, improves the battery's multiplier performance and circulation performance, and improves the capacity reservation rate of lithium sulfur batteries and the capacity of the first circle discharge ratio.
Smart Images

Figure CN119361624A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode material for a photovoltaic lithium-sulfur battery and a preparation method and application thereof, belonging to the technical field of batteries. Background Art
[0002] At present, fossil energy is facing depletion and overuse, which has caused a series of serious environmental problems. It is crucial to develop clean new energy and new efficient energy storage technologies to match it. As a green energy, solar energy has been widely studied for its advantages of being green, environmentally friendly and inexhaustible, and "photovoltaic + energy storage" will become one of the ultimate solutions to energy problems. At present, lithium-ion batteries have become the mainstream of photovoltaic energy storage batteries, but with the expansion of the scale of photovoltaic power stations and the increasing demand, the requirements for energy storage batteries are also getting higher and higher, and lithium-ion batteries can no longer meet the demand for high energy density. Lithium-sulfur batteries have low cost and theoretical energy density (2600Wh kg -1 ) and other advantages, and is considered to be the most promising next-generation rechargeable battery. At present, the main problem restricting the commercialization of lithium-sulfur batteries is the shuttle effect caused by polysulfides during the battery charging and discharging process. During the discharge process, elemental sulfur (S8) is reduced to long-chain lithium polysulfides (Li2S) that are easily soluble in ether liquid electrolytes. x , x = 4 to 8), the dissolved lithium polysulfide will pass from the positive electrode side of the separator to the negative electrode side, and react irreversibly with the metal lithium negative electrode, resulting in the loss of active substances and the deterioration of the surface environment of the lithium negative electrode. At the end of discharge, lithium polysulfide is deposited on the positive electrode surface as insulating Li2S2 or Li2S, blocking the ion / electronic conductivity. Therefore, inhibiting the shuttle effect of long-chain lithium polysulfide is the key to achieving high-capacity and long-cycle lithium-sulfur batteries. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a positive electrode material for photovoltaic lithium-sulfur batteries, a preparation method and application thereof. The technical problem to be solved is to use carbon nanotubes as the matrix material, deposit molybdenum carbide nanoparticles on the inside and outside of the carbon nanotubes, and directly contact with the active substance to the greatest extent. By limiting the dissolution of polysulfides into ether electrolytes through physical and chemical effects, the shuttling effect of polysulfides can be better improved.
[0004] To achieve the above-mentioned object, the present invention provides a positive electrode material for a photovoltaic lithium-sulfur battery, wherein the positive electrode material for a photovoltaic lithium-sulfur battery comprises a matrix and elemental sulfur, wherein the matrix is loaded with elemental sulfur; wherein the matrix comprises carbon nanotubes and molybdenum carbide nanoparticles embedded in the carbon nanotubes.
[0005] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0006] Preferably, in the aforementioned positive electrode material for photovoltaic lithium-sulfur batteries, the diameter of the carbon nanotubes is 30-50 nm, and the thickness of the tube wall is 10 nm; the particle size of the molybdenum carbide nanoparticles is 2-30 nm.
[0007] Preferably, in the aforementioned positive electrode material for photovoltaic lithium-sulfur batteries, the mass ratio of the matrix to elemental sulfur is 1:9 to 4:6.
[0008] Preferably, in the aforementioned positive electrode material for photovoltaic lithium-sulfur batteries, the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes is 0.05:0.95 to 0.25:0.75.
[0009] Preferably, in the aforementioned positive electrode material for photovoltaic lithium-sulfur batteries, the molybdenum carbide nanoparticles are deposited on the inside and outside of the carbon nanotubes.
[0010] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery, comprising the following steps:
[0011] Preparation of substrate; loading elemental sulfur on the substrate.
[0012] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0013] Preferably, the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries comprises the following steps:
[0014] S1: adding ammonium molybdate tetrahydrate into deionized water, stirring continuously until the ammonium molybdate tetrahydrate is completely dissolved, and then adding carbon nanotubes and stirring evenly;
[0015] S2: centrifuging the liquid obtained in step S1 to obtain a precipitate, and drying the precipitate;
[0016] S3: calcining the dried product of step S2 under an inert gas condition to obtain molybdenum carbide / carbon nanotubes;
[0017] S4: The molybdenum carbide / carbon nanotubes obtained in step S3 and elemental sulfur are loaded with sulfur by melt diffusion to obtain the positive electrode material for the photovoltaic lithium-sulfur battery.
[0018] Preferably, in the above-mentioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the concentration of the ammonium molybdate tetrahydrate in step S1 is 10 to 50 mmol L -1 .
[0019] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the centrifugal rotation speed in step S2 is 2000-6000 r / min.
[0020] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the drying temperature in step S2 is 30-70°C.
[0021] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the drying time in step S2 is 12 hours to 30 hours.
[0022] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the calcination temperature in step S3 is 500-800°C.
[0023] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the calcination time in step S3 is 0.5h to 4h.
[0024] Preferably, in the aforementioned method for preparing anode materials for photovoltaic lithium-sulfur batteries, the particle size of the Mo2C particles in step S3 is 2 nm to 30 nm.
[0025] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the inert gas in step S3 is high-purity argon gas with a purity of 99.99%.
[0026] Preferably, in the aforementioned method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries, the parameters of the melt diffusion in step S4 are set as follows: the temperature is 130-170° C., and the time is 6-24 hours.
[0027] The purpose of the present invention and the technical problems solved by the present invention can also be achieved by the following technical measures. A photovoltaic lithium-sulfur battery proposed in the present invention comprises a positive electrode, wherein the positive electrode adopts a positive electrode material for photovoltaic lithium-sulfur batteries; the positive electrode material for photovoltaic lithium-sulfur batteries comprises a matrix and elemental sulfur, wherein the matrix is loaded with elemental sulfur; wherein the matrix comprises carbon nanotubes and dimolybdenum carbide nanoparticles deposited on the carbon nanotubes.
[0028] Compared with the prior art, the positive electrode material for photovoltaic lithium-sulfur batteries and the preparation method and application thereof described in the present invention have the following beneficial effects:
[0029] The present invention uses carbon nanotubes as the matrix material, deposits dimolybdenum carbide nanoparticles on the inner and outer sides of the carbon nanotubes, and directly contacts the active material to the greatest extent. The polysulfide is restricted from dissolving into the ether electrolyte through physical and chemical effects, and the shuttle effect of the polysulfide can be better improved, thereby improving the battery rate performance and cycle performance.
[0030] The photovoltaic lithium-sulfur battery of the present invention has a capacity retention rate of 74-80% after 1000 cycles at a current density of 1C, a first-cycle discharge specific capacity at a current density of 0.2C of 1018-1156 mAh / g, a first-cycle discharge specific capacity at a current density of 0.5C of 943-1093 mAh / g, a first-cycle discharge specific capacity at a current density of 1C of 887-1015 mAh / g, a first-cycle discharge specific capacity at a current density of 2C of 684-828 mAh / g, and a first-cycle discharge specific capacity at a current density of 5C of 592-683 mAh / g.
[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the positive electrode material for photovoltaic lithium-sulfur batteries of the present invention;
[0033] Figure 2 The present invention is a flow chart of the method for preparing the positive electrode material for photovoltaic lithium-sulfur batteries. DETAILED DESCRIPTION
[0034] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a photovoltaic lithium-sulfur battery positive electrode material and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0035] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0036] See also Figure 1 Some embodiments of the present invention provide a positive electrode material for a photovoltaic lithium-sulfur battery, the positive electrode material for a photovoltaic lithium-sulfur battery comprising a substrate and elemental sulfur 3, the substrate being loaded with elemental sulfur 3, the substrate comprising carbon nanotubes (CNTs) 1 and molybdenum carbide (Mo2C) nanoparticles 2 deposited on the carbon nanotubes 1. The elemental sulfur 3 is evenly dispersed on the tube wall of the carbon nanotube, and there is an intermolecular force between the two.
[0037] In some embodiments, optionally, the diameter of the carbon nanotube is 30-50 nm, and the wall thickness is 10 nm; the particle size of the molybdenum carbide nanoparticles is 2-30 nm.
[0038] In some embodiments, optionally, the molybdenum carbide nanoparticles are deposited on the inner and outer sides of the carbon nanotubes, so that they can directly contact with the active material to the greatest extent, and limit the dissolution of polysulfides into the ether electrolyte through physical and chemical effects, which can better improve the shuttle effect of polysulfides and improve the battery rate performance and cycle performance.
[0039] In some embodiments, optionally, the elemental S serves as the positive electrode to provide capacity, and the matrix serves as an additive to provide conductivity and catalytic performance, so that the two have an optimal ratio; the mass ratio of the matrix and elemental sulfur can be 1:9 to 4:6, for example 1:9, 2:8, 3:7, 4:6. If the mass ratio of the two is less than 1:9, the matrix is too little, and the conductivity and catalytic performance provided are insufficient, affecting the performance; if the mass ratio of the two is greater than 4:6, the matrix is excessive, which increases the weight and volume of the positive electrode side and reduces the specific capacity and volume capacity; preferably, it is 2:8. The preferred ratio can provide sufficient conductivity and catalytic performance without reducing the capacity.
[0040] In some embodiments, optionally, the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes is 0.05:0.95 to 0.25:0.75, for example, it can be 0.05:0.95, 0.1:0.9, 0.15:0.85, 0.2:0.8, 0.25:0.75, preferably 0.15:0.85; if the mass ratio of the two is less than 0.05:0.95, the molybdenum carbide nanoparticles are too few and cannot fully play a catalytic role; if the mass ratio of the two is greater than 0.25:0.75, on the one hand, the size of the molybdenum carbide nanoparticles becomes larger, which will make its specific surface area smaller, and the contact area with polysulfide becomes smaller, affecting the catalytic performance; on the other hand, the excess molybdenum carbide nanoparticles will increase the weight of the battery, resulting in a decrease in specific capacity.
[0041] See also Figure 2 Some embodiments of the present invention provide a method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery, comprising the following steps:
[0042] Preparation of substrate; loading elemental sulfur on the substrate.
[0043] In specific implementation, the preparation method comprises the following steps:
[0044] S1: Ammonium molybdate tetrahydrate ((NH4)6Mo7O 244H2O (which is a molybdenum source) is placed in a beaker filled with deionized water and stirred continuously until ammonium molybdate tetrahydrate is completely dissolved, and then carbon nanotubes (CNTs) are added and stirred evenly;
[0045] S2: centrifuging the liquid obtained in step S1 to obtain a precipitate, and drying the precipitate in a vacuum drying oven;
[0046] S3: calcining the dried product of step S2 under inert gas conditions to obtain a matrix of molybdenum carbide / carbon nanotubes (Mo2C / CNTs matrix);
[0047] S4: The matrix molybdenum carbide / carbon nanotubes obtained in step S3 and elemental sulfur are loaded with sulfur by melt diffusion to obtain Mo2C / CNTs / S positive electrode material, that is, the positive electrode material for the photovoltaic lithium-sulfur battery.
[0048] In some embodiments, in order to select a suitable mass ratio between molybdenum carbide and carbon nanotubes, optionally, the concentration of ammonium molybdate tetrahydrate in step S1 can be 10 to 50 mmol / L -1 , for example, 10, 20, 30, 40, 50 mmol L -1 , through experimental data, it was found that adding 30mmol L -1 The rate and cycle performance are the best, so 30mmolL -1 .
[0049] In some embodiments, optionally, the centrifugal speed in step S2 is 2000-6000 r / min, and the solid is sunk to the bottom by the centrifuge to facilitate separation from the liquid.
[0050] In some embodiments, optionally, the drying temperature in step S2 is 30-70° C. If the drying temperature is less than 30° C., the drying effect is relatively poor; if the drying temperature is greater than 70° C., it will cause over-drying, increasing time and energy costs; therefore, considering complete drying, 60° C. is preferred.
[0051] In some embodiments, optionally, the drying time in step S2 is 12 hours to 30 hours. If the drying time is less than 12 hours, the drying effect is relatively poor; if the drying time is greater than 30 hours, it will cause over-drying, increasing time and energy costs; for this reason, considering complete drying, 24 hours is preferred.
[0052] In some embodiments, optionally, the calcination temperature in step S3 is 500-800°C, and this temperature range is selected to ensure that ammonium molybdate tetrahydrate reacts with carbon nanotubes to form dimolybdenum carbide. If it is lower than 500°C, the reaction between molybdenum and carbon is incomplete and molybdenum will remain; if it is higher than 800°C, the energy cost will increase.
[0053] In some embodiments, ammonium molybdate tetrahydrate and carbon nanotubes need to react at high temperature, and the reaction takes time. Optionally, the calcination time in step S3 can be set to 0.5h to 4h. If it is less than 0.5h, the time is too short and the reaction is incomplete; if it is greater than 4h, the time is too long and materials will be wasted; considering the sufficient reaction to be complete, the calcination time can be preferably 2h;
[0054] Different concentrations of ammonium salts will produce different sizes of dimolybdenum carbide particles. In some embodiments, optionally, the particle size of the dimolybdenum carbide particles described in step S3 is 2nm to 30nm, preferably 5nm, so that the cycle performance and rate performance of the battery are better; the particle size is related to the amount of ammonium molybdate tetrahydrate used.
[0055] In some embodiments, optionally, the inert gas in step S3 is high-purity argon gas with a purity of 99.99%.
[0056] The melting temperature of elemental sulfur is above 120°C, and in order to ensure that elemental sulfur has enough time to melt and diffuse evenly. In some embodiments, optionally, the parameters of the melting and diffusion in step S4 are set as follows: the temperature is 130-170°C, preferably 155°C; the time is 6-24h, preferably 12h.
[0057] In some embodiments, optionally, the elemental sulfur loading in step S4 is 60-90%, which is closely related to the ratio of the matrix 2 and the elemental sulfur 1.
[0058] In the above technical scheme, the present invention controls the uniform deposition of molybdenum carbide nanoparticles on carbon nanotubes; the carbon nanotubes suppress the shuttle effect of polysulfides through physical barrier effect, thereby improving the cycle performance and rate performance; the molybdenum carbide nanocatalyst adsorbs polysulfides through chemical action, catalytically accelerates the reaction kinetics of polysulfides, effectively suppresses the shuttle effect, and improves the utilization rate of the active sulfur positive electrode; a multifunctional matrix material is designed by an in-situ synthesis method to uniformly deposit molybdenum carbide nanoparticles on carbon nanotubes; the multifunctional matrix simultaneously has the functions of physical barrier, chemical adsorption and improving reaction kinetics, thereby effectively suppressing the shuttle effect of polysulfides.
[0059] Some embodiments of the present invention further provide a photovoltaic lithium-sulfur battery, comprising a positive electrode, wherein the positive electrode adopts the positive electrode material for photovoltaic lithium-sulfur battery mentioned above.
[0060] The present invention is further described below in conjunction with specific embodiments.
[0061] Example 1
[0062] See also Figure 1, this embodiment provides a positive electrode material for a photovoltaic lithium-sulfur battery, the positive electrode material for a photovoltaic lithium-sulfur battery includes a substrate and elemental sulfur 3, the substrate is loaded with elemental sulfur 3; the substrate includes carbon nanotubes 1 and molybdenum carbide nanoparticles 2; wherein the diameter of the carbon nanotubes is 30-50nm, and the thickness of the tube wall is 10nm; the particle size of the molybdenum carbide nanoparticles is 5nm, and the loading rate of the elemental sulfur 3 is 80%; the mass ratio of the substrate to the elemental sulfur 3 is 2:8; the mass ratio of the molybdenum carbide nanoparticles 2 to the carbon nanotubes 1 is 0.15:0.85;
[0063] The preparation method of the positive electrode material for the above photovoltaic lithium-sulfur battery is shown in Figure 2 , including the following steps:
[0064] S1: Weigh a certain amount of ammonium molybdate tetrahydrate and place it in a beaker filled with deionized water. Continue stirring until the ammonium molybdate tetrahydrate is completely dissolved. The concentration of ammonium molybdate tetrahydrate is 30 mmol L -1 50 ml of transparent colorless liquid was added, and then 150 mg of carbon nanotubes was added and stirred evenly;
[0065] S2: centrifuge the liquid obtained in step S1 at 4000 r / min to obtain a precipitate, and place the precipitate in a vacuum drying oven and dry it at 60° C. for 24 hours;
[0066] S3: calcining the dried product of step S2 at 700° C. for 2 h under an inert gas condition to obtain molybdenum carbide / carbon nanotubes;
[0067] S4: The molybdenum carbide / carbon nanotubes obtained in step S3 and elemental sulfur are loaded with sulfur (12 hours) in an oven at 155° C. by a melt diffusion method to obtain Mo2C / CNTs / S, i.e., the positive electrode material for the photovoltaic lithium-sulfur battery; the weight ratio of Mo2C / CNTs to elemental S is 2:8.
[0068] Example 2
[0069] The difference between this embodiment and embodiment 1 is that the mass ratio of the matrix and the elemental sulfur 3 in this embodiment is 1:9, and the loading rate of the elemental sulfur 3 is 90%; the other parameters and steps are the same as those in embodiment 1.
[0070] Example 3
[0071] The difference between this embodiment and embodiment 1 is that the mass ratio of the matrix and the elemental sulfur 3 in this embodiment is 3:7, and the loading rate of the elemental sulfur 3 is 70%; the remaining parameters and steps are the same as those in embodiment 1.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 1 is that the mass ratio of the matrix and the elemental sulfur 3 in this embodiment is 4:6, and the loading rate of the elemental sulfur 3 is 60%; the remaining parameters and steps are the same as those in embodiment 1.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the mass ratio of the dimolybdenum carbide nanoparticles to the carbon nanotubes in this embodiment is 0.05:0.95, and the other parameters and steps are the same as those in embodiment 1.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes in this embodiment is 0.1:0.9, and the other parameters and steps are the same as those in embodiment 1.
[0078] Example 7
[0079] The difference between this embodiment and embodiment 1 is that the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes in this embodiment is 0.2:0.8, and the other parameters and steps are the same as those in embodiment 1.
[0080] Example 8
[0081] The difference between this embodiment and embodiment 1 is that the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes in this embodiment is 0.25:0.75, and the other parameters and steps are the same as those in embodiment 1.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that the mass ratio of the matrix to the elemental sulfur 3 in this comparative example is 1:10, and the loading rate of the elemental sulfur 3 is 90.9%; the other parameters and steps are the same as those in Example 1.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that the mass ratio of the matrix to the elemental sulfur 3 in this comparative example is 5:6, and the loading rate of the elemental sulfur 3 is 54.5%; the other parameters and steps are the same as those in Example 1.
[0086] Comparative Example 3
[0087] The difference between this comparative example and Example 1 is that the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes in this comparative example is 0.05:1.00, and the other parameters and steps are the same as those in Example 1.
[0088] Comparative Example 4
[0089] The difference between this comparative example and Example 1 is that the mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes in this comparative example is 0.25:0.70, and the other parameters and steps are the same as those in Example 1.
[0090] Comparative Example 5
[0091] The difference between this comparative example and Example 1 is that the substrate in this comparative example is molybdenum carbide nanoparticles, and the other parameters and steps are the same as Example 1.
[0092] Comparative Example 6
[0093] The difference between this comparative example and Example 1 is that the substrate in this comparative example is carbon nanotubes, and the other parameters and steps are the same as Example 1.
[0094] Comparative Example 7
[0095] The difference between this comparative example and Example 1 is that this comparative example does not contain a matrix, and elemental sulfur 3 is directly used as the positive electrode material for photovoltaic lithium-sulfur batteries.
[0096] The sulfur positive electrode, separator, electrolyte and lithium negative electrode prepared in the above Examples 1-8 and Comparative Examples 1-7 were assembled into a photovoltaic lithium-sulfur battery, and its electrochemical performance, including rate performance and cycle performance, was tested. The test results are shown in Table 1. The charge and discharge voltage for testing the electrochemical performance was set to 1.7V-2.8V. In the rate performance test, the current density was set to 0.2C, 0.5C, 1C, 2C, 5C, and 0.2C, respectively.
[0097] Table 1
[0098]
[0099]
[0100] It can be seen from the data in Table 1 that the photovoltaic lithium-sulfur batteries of Examples 1-8 of the present invention have a capacity retention rate of 74-80% after 1000 cycles at a current density of 1C, a first-cycle discharge capacity of 1018-1156 mAh / g at a current density of 0.2C, a first-cycle discharge capacity of 943-1093 mAh / g at a current density of 0.5C, a first-cycle discharge capacity of 887-1015 mAh / g at a current density of 1C, a first-cycle discharge capacity of 684-828 mAh / g at a current density of 2C, and a first-cycle discharge capacity of 592-683 mAh / g at a current density of 5C. Among them, the first-cycle discharge capacity at a current density of 0.2C can reach up to 1156 mAh / g. In the cycle performance test, the capacity retention rate was 80% after 1000 cycles at a current density of 1C.
[0101] Compared with Example 1, as the mass ratio of the carbon material matrix and elemental sulfur decreases, the capacity retention rate of Example 2 after 1000 cycles at 1C current density, the first cycle discharge capacity at 0.2C current density, the first cycle discharge capacity at 0.5C current density, the first cycle discharge capacity at 1C current density, and the first cycle discharge capacity at 5C current density are reduced; at this time, the elemental S loading rate is too high, and the carbon material matrix is insufficient to provide sufficient conductivity and catalysis, resulting in reduced electrochemical performance. As the mass ratio of the matrix and elemental sulfur increases, the capacity retention rate of Examples 3 and 4 after 1000 cycles at 1C current density, the first cycle discharge capacity at 0.2C current density, the first cycle discharge capacity at 0.5C current density, the first cycle discharge capacity at 1C current density, and the first cycle discharge capacity at 5C current density are reduced; at this time, the elemental S loading rate is too low, resulting in excess carbon material matrix, increasing the volume and weight of the positive electrode material, resulting in reduced electrochemical performance.
[0102] Compared with Example 1, as the mass ratio of Mo2C nanoparticles to carbon nanotubes decreases, the capacity retention rate of 1000 cycles at 1C current density, the first cycle discharge specific capacity at 0.2C current density, the first cycle discharge specific capacity at 0.5C current density, the first cycle discharge specific capacity at 1C current density, and the first cycle discharge specific capacity at 5C current density of Examples 5 and 6 decrease; at this time, the content of Mo2C nanoparticles is too small to provide sufficient catalytic performance, resulting in reduced electrochemical performance. As the mass ratio of Mo2C nanoparticles to carbon nanotubes increases, the capacity retention rate of 1000 cycles at 1C current density, the first cycle discharge specific capacity at 0.2C current density, the first cycle discharge specific capacity at 0.5C current density, the first cycle discharge specific capacity at 1C current density, and the first cycle discharge specific capacity at 5C current density of Examples 7 and 8 decrease; at this time, the content of Mo2C nanoparticles is too high, resulting in the enlargement of Mo2C nanoparticles, the reduction of specific surface area, and the deterioration of catalytic performance. At the same time, the excessive content of Mo2C nanoparticles increases the weight of the positive electrode material, resulting in reduced electrochemical performance.
[0103] Compared with Example 1, as the mass ratio of the carbon material matrix and elemental sulfur decreases and the mass ratio of the two is not within the protection scope of the present invention, the capacity retention rate of 1000 cycles at a current density of 1C, the first-cycle discharge specific capacity at a current density of 0.2C, the first-cycle discharge specific capacity at a current density of 0.5C, the first-cycle discharge specific capacity at a current density of 1C, and the first-cycle discharge specific capacity at a current density of 5C in Example 1 decrease; as the mass ratio of the carbon material matrix and elemental sulfur increases and the mass ratio of the two is not within the protection scope of the present invention, the capacity retention rate of 1000 cycles at a current density of 1C, the first-cycle discharge specific capacity at a current density of 0.2C, the first-cycle discharge specific capacity at a current density of 0.5C, the first-cycle discharge specific capacity at a current density of 1C, and the first-cycle discharge specific capacity at a current density of 5C in Example 2 significantly decrease; elemental S is used as the positive electrode, and its load rate directly affects the electrochemical properties of the battery.
[0104] Compared with Example 1, as the mass ratio of the Mo2C nanoparticles to the carbon nanotubes is reduced to 0.05:1.00 and it is not within the scope of protection of the present invention, the capacity retention rate of 1000 cycles at 1C, the first cycle discharge capacity at 0.2C, the first cycle discharge capacity at 0.5C, the first cycle discharge capacity at 1C and the first cycle discharge capacity at 5C of the comparative example 3 are reduced; as the grinding time described in step S2 increases and it is not within the scope of protection of the present invention, the capacity retention rate of 1000 cycles at 1C, the first cycle discharge capacity at 0.2C, the first cycle discharge capacity at 0.5C, the first cycle discharge capacity at 1C and the first cycle discharge capacity at 5C of the comparative example 4 are significantly reduced. Under the condition of a certain elemental sulfur loading rate, the mass ratio of the Mo2C nanoparticles to the carbon nanotubes directly affects the electrochemical performance of the battery.
[0105] Compared with Example 1, Comparative Example 5 does not contain carbon nanotubes, and molybdenum carbide nanoparticles are directly used as the matrix. Its capacity retention rate after 1000 cycles at 1C, the first-cycle discharge specific capacity at a current density of 0.2C, the first-cycle discharge specific capacity at a current density of 0.5C, the first-cycle discharge specific capacity at a current density of 1C, and the first-cycle discharge specific capacity at a current density of 5C are significantly reduced; carbon nanotubes provide conductivity for the single substance S during the redox reaction. When carbon nanotubes are not included, the poor conductivity leads to a low depth of the redox reaction and a low discharge specific capacity. Comparative Example 6 does not contain Mo2C nanoparticles. Mo2C nanoparticles are directly used as a matrix. Its capacity retention rate after 1000 cycles at a current density of 1C, the first cycle discharge capacity at a current density of 0.2C, the first cycle discharge capacity at a current density of 0.5C, the first cycle discharge capacity at a current density of 1C, and the first cycle discharge capacity at a current density of 5C are significantly reduced; Mo2C nanoparticles are used as a catalyst to improve the reaction kinetics of elemental S during the redox reaction. When Mo2C nanoparticles are not included, the reaction kinetics during the redox reaction is slow and the discharge capacity is low. Comparative Example 7 does not contain a matrix. Elemental sulfur is directly used as the sulfur positive electrode material for energy storage batteries. Its capacity retention rate after 1000 cycles at a current density of 1C, the first cycle discharge capacity at a current density of 0.2C, the first cycle discharge capacity at a current density of 0.5C, the first cycle discharge capacity at a current density of 1C, and the first cycle discharge capacity at a current density of 5C are significantly reduced. Elemental S has poor conductivity, and the reaction kinetics of the redox reaction during the charge and discharge process are slow, resulting in a low discharge capacity.
[0106] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0107] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0108] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0109] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0110] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A positive electrode material for photovoltaic lithium-sulfur batteries, characterized in that: The positive electrode material for photovoltaic lithium-sulfur cells comprises a substrate and elemental sulfur, wherein the substrate is loaded with elemental sulfur; wherein the substrate comprises carbon nanotubes and molybdenum carbide nanoparticles deposited on the carbon nanotubes.
2. The positive electrode material for photovoltaic lithium-sulfur batteries according to claim 1, characterized in that: The diameter of the carbon nanotube is 30-50nm, and the thickness of the tube wall is 10nm; the particle size of the molybdenum carbide nanoparticles is 2-30nm; and the molybdenum carbide nanoparticles are deposited on the inner side and the outer side of the carbon nanotube.
3. The positive electrode material for photovoltaic lithium-sulfur batteries according to claim 1, characterized in that: The mass ratio of the matrix to elemental sulfur is 1:9 to 4:
6.
4. The positive electrode material for photovoltaic lithium-sulfur batteries according to claim 1, characterized in that: The mass ratio of the molybdenum carbide nanoparticles to the carbon nanotubes is 0.05:0.95 to 0.25:0.
75.
5. A method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery, characterized in that: The following steps are involved: Preparation of substrate; loading elemental sulfur on the substrate.
6. The method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery according to claim 5, characterized in that: The preparation method comprises the following steps: S1: adding ammonium molybdate tetrahydrate into deionized water, stirring continuously until the ammonium molybdate tetrahydrate is completely dissolved, and then adding carbon nanotubes and stirring evenly; S2: centrifuging the liquid obtained in step S1 to obtain a precipitate, and drying the precipitate; S3: calcining the dried product of step S2 under an inert gas condition to obtain molybdenum carbide / carbon nanotubes; S4: The molybdenum carbide / carbon nanotubes obtained in step S3 and elemental sulfur are loaded with sulfur by melt diffusion to obtain the positive electrode material for the photovoltaic lithium-sulfur battery.
7. The method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery according to claim 6, characterized in that: The concentration of ammonium molybdate tetrahydrate in step S1 is 10 to 50 mmol L -1 ; The centrifugal speed in step S2 is 2000-6000r / min; the drying temperature is 30-70°C; the drying time is 12h-30h.
8. The method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery according to claim 6, characterized in that: The calcination temperature in step S3 is 500-800° C.; the calcination time is 0.5 h to 4 h; the particle size of the molybdenum carbide particles is 2 nm to 30 nm; and the inert gas is high-purity argon gas with a purity of 99.99%.
9. The method for preparing a positive electrode material for a photovoltaic lithium-sulfur battery according to claim 6, characterized in that: The parameters of the melt diffusion in step S4 are set as follows: temperature is 130-170° C., and time is 6-24 h.
10. A photovoltaic lithium-sulfur battery, characterized in that: It comprises a positive electrode, wherein the positive electrode adopts a positive electrode material for a photovoltaic lithium-sulfur battery; the positive electrode material for a photovoltaic lithium-sulfur battery comprises a matrix and elemental sulfur, wherein the matrix is loaded with elemental sulfur; wherein the matrix comprises carbon nanotubes and molybdenum carbide nanoparticles embedded in the carbon nanotubes.